돼지의 교잡방법이 육의 품질에 미치는 영향 - 진상근; 김일석; 송영민; 허선진; 하지희; 하경희; Jin, S.K; Kim, I.S; Song, Y.M; Hur, S.J; Ha, J.H; Hah, K.H (Journal of animal science and technology, 2005)
A total of 80 pigs were used to investigate the effect of crossbred method on meat quality. Crossbred pigs were alloted into one of two experimental groups[T1 : Landrace ${\times}$ Yorkshire ${\times}$ Duroc(LYD) and T2: Yorkshire ${\times}$ Berkshire ${\times}$ Berkshire(YBB)]. Crossbred pigs were slaughtered at approximately 110kg live weight, and pH, cooking loss, texture, shear force, color(CIE $L^*$ $a^*$ $b^*$), fatty acid composition and sensory evaluation were measured in pork loin. Crude fat percentage was higher in YBB, whereas protein was higher in LYD than that for the other groups. Shear force was lower in YBB than LYD, but, pH and water-holding capacity were not significantly different. In meat color, $L^*$ was higher in YBB than LYD, whereas $a^*$ and $b^*$ were not significantly different between breeds. Hardness, adhesiveness and gumminess of YBB were significantly lower than LYD. Saturated fatty acid of YBB was lower than that for LYD and essential fatty acid was higher in YBB. In sensory evaluation of cooked meat, color, marbling score and overall acceptability were significantly higher in YBB, Aroma, flavor, taste, juiciness and overall acceptability of YBB were significantly higher than LYD in fresh meat. In conclusion, the overall meat quality was better in YBB than that for LYD.